2021
DOI: 10.1007/s13278-021-00753-z
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 fake news diffusion across Latin America

Abstract: Fact-checking verifies a multitude of claims and remains a promising solution to fight fake news. The spread of rumors, hoaxes, and conspiracy theories online is evident in times of crisis, when fake news ramped up across platforms, increasing fear and confusion among the population as seen in the COVID-19 pandemic. This article explores fact-checking initiatives in Latin America, using an original Markov-based computational method to cluster topics on tweets and identify their diffusion between different data… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 52 publications
0
15
1
4
Order By: Relevance
“…However, this does not agree with a study that evaluated the HPV vaccine hesitancy among parents in Italy, which found no difference between knowing that the HPV vaccine was a preventive measure for this disease and educational level [37]. This could be explained by an infodemic that occurred in LAC countries during 2020 [38,39] and could equally affect people of different educational levels.…”
Section: Discussioncontrasting
confidence: 71%
“…However, this does not agree with a study that evaluated the HPV vaccine hesitancy among parents in Italy, which found no difference between knowing that the HPV vaccine was a preventive measure for this disease and educational level [37]. This could be explained by an infodemic that occurred in LAC countries during 2020 [38,39] and could equally affect people of different educational levels.…”
Section: Discussioncontrasting
confidence: 71%
“…A reason for this includes the overwhelming amount of news connected to treatment solutions for COVID‐19, usually originating from social media platforms. Fake news started gaining political value within the region, tempting individuals to make false claims or reach for ineffective solutions to the pandemic [ 68 ]. Trends of increased COVID‐19 mortality in LAC have been linked to higher use and trust of social media as a means of obtaining health information [ 69 ].…”
Section: “Miracle” Drugs and Infodemiamentioning
confidence: 99%
“…Therefore, it is not surprising that, in this study, people who have social networks as their main source of information have the lowest intention to be vaccinated against COVID-19. A previous study indicated that the proportion of misinformation about vaccines was higher in Brazil, Colombia and Venezuela than in other Latin American countries (Ceron et al, 2021 ). This could be associated with the ease of social networks to spread inaccurate information about the safety of COVID-19 vaccines (Wilson & Wiysonge, 2020 ).…”
Section: Discussionmentioning
confidence: 95%